Associations of Midlife Leukocyte Telomere Length With Measures of Left Atrial Function in Community‐Dwelling Older Adults: The ARIC Study - Parikh, Romil R.; Pankratz, Nathan; Lane, John A.; Arking, Dan E.; Eaton, Anne; Chen, Lin Yee; Lutsey, Pamela L.; Tang, Weihong (Journal of the American Heart Association, 2025)
It is unknown whether atrial myopathy, ascertained by poor left atrial (LA) function, is associated with biological aging independent of chronological age. Such an association would indicate that atrial myopathy may be preventable by intervening on modifiable risk factors that accelerate aging. Therefore, we evaluated associations of midlife leukocyte telomere length (LTL, a measure of biological aging) with measures of LA function (a surrogate for LA myopathy). We included 4376 adults (mean age, 75 years; 41.11% men; 16.36% Black individuals) from the ARIC (Atherosclerosis Risk in Communities) study. We measured LA function as LA reservoir, conduit, and contractile strain using 2-dimensional speckle tracking echocardiography (2011-2013). We used TelSeq software to estimate LTL from whole genome sequencing data collected in midlife (1987-1998; mean age, 55 years). LTL estimates were inverse normalized within read length group and whole genome sequencing platform before being merged. We used linear regression to estimate the associations of LTL with LA function. LTL was weakly correlated with chronological age at blood draw for LTL measurement ( =-0.12; <0.001). In models adjusted for chronological age at blood draw for LTL measurement, whole genome sequencing platform, visit for blood draw, cardiometabolic risk factors, and coronary heart disease, longer LTL was associated with greater (better) LA contractile strain (β=0.29 [95% CI, 0.10-0.47]; =0.006) and LA reservoir strain (β=0.35 [95% CI, 0.12-0.59]; =0.003) but not LA conduit strain (β=0.05 [95% CI, -0.12 to 0.21]; =0.575). Greater biological aging may adversely impact LA substrate independent of chronological aging.